Sex-related differences in clinical outcomes and quality of life after transcatheter aortic valve implantation for severe aortic stenosis - Bagienski, Maciej; Tokarek, Tomasz; Wiktorowicz, Agata; Dziewierz, Artur; Rzeszutko, Lukasz; Sorysz, Danuta; Kleczynski, Pawel; Dudek, Dariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction: There are inconsistent data on the sex-related differences in clinical outcomes and quality of life (QoL) after transcatheter aortic valve implantation (TAVI). Aim: We sought to investigate sex-related differences in procedural, clinical and QoL outcomes of TAVI. Material and methods : A total of 101 consecutive patients undergoing TAVI were enrolled. Patients were stratified by gender. Baseline characteristics, procedural and long-term clinical outcomes as well as frailty and QoL indices (EQ-5D-3L questionnaire) were compared between women and men. Results: Women represented 60.4% of the study population. Periprocedural risk measured with the Logistic EuroSCORE and STS scale was similar for women and men. There were no differences in 30-day or 12-month all-cause mortality between groups (women vs. men: 9.8% vs. 12.5%; age-adjusted odds ratio (OR) (95% CI): 1.38 (0.39–4.94); 13.1% vs. 25.0%; age-adjusted OR (95% CI): 2.51 (0.87–7.25)). Men were at higher risk of new onset atrial fibrillation at follow-up (1.6% vs. 17.5%; age-adjusted OR (95% CI): 14.61 (1.68–127.37)). In multivariable Cox regression analysis, a history of stroke/transient ischemic attack (TIA) (hazard ratio (HR)) (95% CI): 3.93 (1.39–11.07) and blood transfusion (HR (95% CI): 2.84 (1.06–7.63)) were identified as independent factors affecting 12-month mortality. No differences in QoL parameters were noted. Conclusions : The TAVI can be considered as an effective and safe treatment in high-risk patients with severe aortic stenosis, regardless of gender.